Networking of CD/DVD-ROMS–An Overview - Satish Kumar, K.; Jayaraman, P.O. (DESIDOC Journal of Library & Information Technology, 2003)
As the collection of CDs/DVD ROMs increases in a library, it becomes important for the librarian to manage and share them effectively. This article discusses the benefits of sharing CD/DVD-ROMs over a network and introduces device called CD libraries/servers for sharing CD title discs over a network. It takes a look at architecture and available technologies for above purpose and concludes by giving an overview of technologies and facilities available at LRDE library. http://dx.doi.org/10.14429/dbit.22.6.3577